Structural phase transition and magnetism in hexagonal SrMnO3 by magnetization measurements and by electron, x-ray, and neutron diffraction studies - Daoud-Aladine, A; Martin, C; Chapon, L; Hervieu, M; Knight, K; Brunelli, M; Radaelli, P (2007)
The structural and magnetic properties of the hexagonal four-layer form of SrMn O3 have been investigated by combining magnetization measurements, electron diffraction, and high-resolution synchrotron x-ray and neutron powder diffraction. Below 350 K, there is subtle structural phase transition from hexagonal symmetry (space group P 63/mmc) to orthorhombic symmetry (space group C 2221) where the hexagonal metric is preserved. The second-order phase transition involves a slight tilting of the corner-sharing Mn2 O9 units composed of two face-sharing Mn O6 octahedra and the associated displacement of Sr2+ cations. The phase transition is described in terms of symmetry-adapted displacement modes of the high symmetry phase. Upon further cooling, long range magnetic order with propagation vector k= (0,0,0) sets in below 300 K. The antiferromagnetic structure, analyzed using representation theory, shows a considerably reduced magnetic moment indicating the crucial role played by direct exchange between Mn centers of the Mn2 O9 units. © 2007 The American Physical Society.